Laboratory Evaluation of the Platelet Component of Hemostasis in acute Coronary Syndrome With ST Segment Elevation - D. Markhulia; K. A. Popugaev; D. A. Sychev; M. V. Vatsik-Gorodetskaya; G. A. Gazaryan; M. A. Godkov; A. A. Kachanova; K. V. Kiselev; E. V. Klychnikova; D. A. Kosolapov; I. M. Kuzmina; K. B. Mirzaev; et al. (Неотложная медицинская помощь)
RELEVANCE. Acute coronary syndrome (ACS) is one of the most common cardiovascular diseases associated with increased mortality and disability of patients. Regarding the factor of genetic resistance to antiplatelet therapy, and we get an even more serious problem faced by cardiologists around the world. The study of antiplatelet therapy and resistance to it is a pressing issue in modern cardiology. This is important not only for determining the effectiveness of treatment for each patient, but also for personalizing therapy based on genetic characteristics. This allows improving the effectiveness of treatment and preventing recurrent cardiovascular complications. As a result, the study of antiplatelet therapy and resistance to it is an important aspect in the treatment of ACS. This helps prevent recurrent cardiovascular complications, improve the effectiveness of treatment and develop new methods of therapy.AIM OF THE STUDY. ST-segment elevation ACS (STEMI) based on a personalized approach to antiplatelet therapy and modification of the program to predict the course and outcome. To study the possibilities of various laboratory diagnostic methods for assessing the platelet component of hemostasis in patients with STEMI depending on (1) the combination of antiplatelet drugs used (aspirin + clopidogrel; aspirin + ticagrelor); (2) the presence of factors of genetic resistance to antiplatelet agents.MATERIAL AND METHODS. The study included patients with STEMI who underwent percutaneous coronary intervention in the infarct-related artery territory , a total of 46 patients (13 women, 33 men) aged 35 to 83 years, average age 61.7 years. Patients were divided into groups according to the received combination of dual antiplatelet therapy (DAPT) aspirin + clopidogrel (23 patients), aspirin + ticagrelor (23 patients), groups with and without genetic determination (GD ) were assessed. The platelet component of hemostasis was assessed in three different ways: standard coagulogram, aggregometry, rotation thromboelasthometry. The following pharmacogenetic markers were determined in all patients: CYP2C19*17, CYP2C19*2, CYP2C19*3, SLCO1B1 , CYP3A5*3 . LOF alleles were detected in 32 patients (67%). Among them, in the group taking aspirin in combination with clopidogrel, three subgroups of patients were distinguished: 7 patients in the slow metabolizer (SM) subgroup, 8 patients in the general rapid metabolizer subgroup , and 8 patients without LOF alleles were designated as normal metabolizers. In the group taking aspirin in combination with ticagrelor, 9 patients with intermediate metabolism were identified. Seven patients in the SM group. Seven patients without LOF alleles were classified as NM group. The course of the disease and its outcomes were assessed.RESULTS. Against the background of the use of antiplatelet agents, at research points 2 and 3, the values of the CT-EXTEM parameter statistically significantly increased compared to research point 1 and went beyond the reference values, reflecting drug-induced hypocoagulation of the platelet hemostasis link (66.1±2 and 96.3±14.3 s, respectively, p=0.02). It was especially important that in the group with GR, the CT-EXTEM parameter did not change either by research point 2 or by research point 3, reflecting platelet normal or hypercoagulation.CONCLUSION. Aggregometry parameters do not allow adequate assessment of the state of the platelet hemostasis link and its response to antiplatelet therapy in patients with acute coronary syndrome with ST segment elevation. Among the studied traditional and viscoelastic hemostatic parameters, the only parameter that should be used to assess the state of the platelet hemostasis link and its response to antiplatelet therapy is the CT-EXTEM test.